Analisis User Interface Pada Aplikasi Potio Dengan Metode Heuristic Evaluation - Justin Edbert; Arianti; Renny (STMIK KHARISMA Makassar, 2026)
Potio is a mobile-based reminder application that can help its users to take vitamins or medicines consistently. This study aims to analyze the User Interface of the Potio application, because the application UI design is limited only by the developer, without involving the application users. The analysis was conducted to determine whether improvements are necessary or not. In this case, the need for improvements is determined from the results of the calculation of questionnaire data for each Heuristic Evaluation principle that has been submitted to expert respondents. From the calculation results using the Severity Rating formula, there are two principles that have a fairly high average Severity Rating value, namely the Help Users Recognize and Recover from Errors principle and the Help and Documentation principle. This second principle has a rounded value of 1, where a value of 1 means that improvements are not really necessary because the problems found do not affect user comfort.